Modeling of hemoglobin in dengue fever and dengue hemorrhagic fever using bioelectrical impedance - Ibrahim, F.; Ismail, N.A.; Taib, M.N.; Wan Abas, W.A.B. (IOP Publishing, 2004)
This paper describes a model for predicting hemoglobin (Hb) by using bioelectrical impedance analysis (BIA) in dengue patients in the Hospital Universiti Kebangsaan Malaysia (HUKM). Bioelectrical impedance measurements were conducted on 83 (47 males and 36 females) serologically confirmed dengue fever (DF) and dengue hemorrhagic fever (DHF) patients during their hospitalization. The predictive equation for Hb was derived using multivariate analysis. We investigated all the parameters in BIA, patients' symptom and demographic data. In this developed model, four predictors (reactance (Xc), sex, weight and vomiting) were found to be the best predictive factors for modeling Hb in dengue patients. However, the model can only explain approximately 42 of the variation in Hb status, thus single frequency bio-impedance stand-alone technique is insufficient to monitor Hb for the DF and DHF patients. Further investigation using multi-frequency BIA is recommended in modeling Hb to achieve the most parsimonious model.